Mechanisms of antimicrobial resistance in Salmonella - Lopes, Graciela Volz; Da Silva, Alessandra Almeida; Pacheco, Daniele Boldan; Da Cunha, Andrielle Dias; Pereira, Ytaiara Lima (Seven Editora, 2023)
Salmonella enterica subsp. enterica is considered one of the most common causes of foodborne illness (FOBD) and animal products are responsible for a significant number of human cases of salmonellosis. In addition to the risk posed by Salmonella as a foodborne pathogen, there is worldwide concern about the emergence of strains resistant to multiple antimicrobial agents. Over the years, several studies have identified genes and mutations conferring antimicrobial resistance in Salmonella isolates, which will be discussed in this chapter. DOI: https://doi.org/10.56238/colleinternhealthscienv1-035